A Relevant Wound-Like in vitro Media to Study Bacterial Cooperation and Biofilm in Chronic Wounds - Pouget, Cassandra; Dunyach-Remy, Catherine; Bernardi, Thierry; Provot, Christian; Tasse, Jason; Sotto, Albert; Lavigne, Jean-Philippe (Frontiers in Microbiology, 2022)
Biofilm on the skin surface of chronic wounds is an important factor in the pathology, inhibiting wound healing. The polymicrobial nature of these infected wounds and bacterial interactions inside this pathogenic biofilm are the keys for understanding chronic infection. The aim of our work was to develop an innovative in vitro medium that closely mimics the chronic wound emphasizing the microbiological, cellular and inflammatory environment of chronic wounds but also focusing on the pH found at the wound level. This new medium, called chronic wound medium (CWM), will thus facilitate the study of pathogenic biofilm organization. Clinical Staphylococcus aureus and Pseudomonas aeruginosa strains co-isolated from diabetic foot infection (DFI) were collected and cultivated in this new medium for 24h in mono- and co-culture. Bacterial growth (growth curves), presence of small colony variant (SCV), biofilm formation (BioFilm Ring Test® assay, biofilm biomass quantification) and virulence (survival curve in a Caenorhabditis elegans model) were evaluated. After 24h in the in vitro conditions, we observed that P. aeruginosa growth was not affected, compared with a control bacterial medium, whereas for S. aureus, the stationary phase was reduced by two logs. Interestingly, S. aureus growth increased when co-cultured with P. aeruginosa in CWM. In co-culture with P. aeruginosa, SCV forms of S. aureus were detected. Biofilm studies showed that bacteria, alone and in combination, formed biofilm faster (as soon as 3h) than the bacteria exposed in a control medium (as soon as 5h). The virulence of all strains decreased in the nematode model when cultivated in our new in vitro medium. Taken together, our data confirmed the impact of the chronic wound environment on biofilm formation and bacteria virulence. They indicated that P. aeruginosa and S. aureus cooperated in co-infected wounds. Therefore, this in vitro model provides a new tool for bacterial cooperation investigation and polymicrobial biofilm formation.